(3GOGQI GdeTQhYGJ GdUZjQI (B:s (3eONd GSJQGJjLj ddefGaSI hGdJejR (B/s - (3GdMSjfj, adGM MSfs ((3YeGf(B: s (3OGQ GdTQhb ddfTQ(B, s, 2006)
(3GTJed gPG GdcJGH Ydi GKfG YTQ aUdkG, djSJYQV GdeaGgje hGdCWQ GdfXQjI hdjMOO eaghe GdQjGOjI hCgejJgG hNUGUgG, hJUOi dehVhY GdeSDhdjI GdGLJeGYjI(B. (3ZWj GdEWGQ GdYGe dOQGSGJ GdLOhi GdGbJUGOjI hGdafjI hGTJed Ydi eaGgje GSJQGJjLjI hGdGOGQI GdGSJQGJjLjI, hjhVM BdjGJ hGLQGAGJ YedjGJ GdJNWjW GdGSJQGJjLj hJfGhd GdLhGfH GdJfXjejI hEYOGO gjGcd hJVef YedjGJ GdEOGQI GdeGdjI aj GdeTQhYGJ GdUZjQI hJfGhd GdehGQO GdHTQjI(B. (3hLGA GdaUd GdYGTQ djJfGhd GdCfTWI GdJShjbjI hUjGZI GdGSJQGJjLjGJ, hJfGhd MhSHI aYGdjGJ gPg GdeTGQjY EVGaI Edi JfGhdg dehVhY Mjhj hgh GdJLGQI GdEdcJQhfjI hCNjQkG JfGhd GdQbGHI Ydi CfTWI GdeTQhY hcjajI Jbhje GdCOGA ajg(B.s
(3HjHdjhZQGajG U(B.s
Keywords: (3GOGQI GYeGds; (3GOGQI eTQhYs; (3JfajP eTQhYs; (3eTGQjYs